Urgensitas Manajemen Lembaga dalam Meningkatkan Kepercayaan Masyarakat - Abd. Wahib (STAIFAS-Press, 2020)
This paper is about the urgency of institutional management in increasing public trust which consists of management functions and applications as well as increasing public trust. Apply management functions in increasing public trust. Madrasah heads, teachers, and employees can carry out their duties properly in increasing public trust which includes: accommodation, cooperation, and assimilation. Application of institutional management in increasing trust in the community is expected to the head of the Madrasa or school to not hesitate to motivate and provide direction in carrying out tasks to subordinates in achieving goals both quality and quantity can be achieved in accordance with shared expectations. To teachers and employees to always be creative and innovative so that the development and progress of the institution is in line with the needs of society and the times. Of course, the hope for students to always be diligent in learning and maintaining the good name of the institution, because the challenges in the future will be more severe, therefore, as the next generation of national fighters must prepare themselves to face life in the future